Comparative Study on the Effect of Cidofovir Treatment for Severe Adenovirus Pneumonia. (December 2021) - Moon, Seong Mi; Choe, Junsu; Na, Soo Jin; Chung, Chi Ryang; Suh, Gee Young; Jeon, Kyeongman
Background: Adenovirus infection can cause severe pneumonia even in immunocompetent adults. However, there is limited data on the benefits of cidofovir treatment in severe adenovirus pneumonia. The objective of this study was to evaluate the association of cidofovir treatment with clinical improvement in immunocompetent adult patients with severe adenovirus pneumonia. Methods: We evaluated 22 male patients who admitted to intensive care unit (ICU) with severe adenovirus pneumonia between January 2014 and December 2019. The patients were divided into 2 groups, patients treated with cidofovir or not. Clinical outcomes including time to defervescence and stopping of oxygen supplement, length of stay in ICU and hospital, and the need for mechanical ventilation (MV) and extracorporeal membrane oxygenation (ECMO) were compared between the 2 groups. Results: Among 22 patients, 13 patients (59%) were treated with cidofovir and 9 (41%) were not. The difference in mean time (95% confidence interval [CI]) to defervescence and stopping of oxygen supplement between cidofovir group and no cidofovir group was 2.1 (−5.7 to 10.0) and 1.0 (−14.9 to 16.8) days, respectively. The difference in mean length of stay (95% CI) in ICU and hospital between the 2 groups was 0.2 (−7.1 to 7.5) and −0.4 (−18.3 to 17.5) days, respectively. The differences in proportion of patients requiring MV and ECMO between the 2 groups was 28.2 (−17.4 to 73.8) % and −10.3 (−52.2 to 31.7) %, respectively. Conclusions: The treatment with cidofovir for severe adenovirus pneumonia in immunocompetent patients did not improve clinical outcomes. Further studies with larger samples with prospective design are warranted.